THE ROLE OF COLOCASIA ESCULENTA IN CANCER PREVENTION AND TREATMENT: A SYSTEMATIC REVIEW OF EPIDEMIOLOGICAL AND EXPERIMENTAL STUDIES - Fahmeeda S; Prabu D; Haripriya R; Sindhu R; Lubna Fathima; Rajmohan M; Dinesh Dhamodhar; Banu Jothi A (The Bioscan, 2026)
Cancer remains a leading global health challenge, with conventional treatments often causing severe side effects. Plant-based bioactives are increasingly explored for safer and cost-effective alternatives. Colocasia esculenta (taro), a traditional food crop, has been studied for its potential anticancer properties.